Microbial survival and growth on non‐corrodible conductive materials. (24th October 2021) - Bird, Lina J.; Tender, Leonard M.; Eddie, Brian; Oh, Eunkeu; Phillips, Daniel A.; Glaven, Sarah M.
Summary: Biofilms growing aerobically on conductive substrates are often correlated with a positive, sustained shift in their redox potential. This phenomenon has a beneficial impact on microbial fuel cells by increasing their overall power output but can be detrimental when occurring on stainless steel by enhancing corrosion. The biological mechanism behind this potential shift is unresolved and a metabolic benefit to cells has not been demonstrated. Here, biofilms containing the electroautotroph ' Candidatus Tenderia electrophaga' catalysed a shift in the open circuit potential of graphite and indium tin oxide electrodes by >100 mV. Biofilms on open circuit electrodes had increased biomass and a significantly higher proportion of ' Ca . Tenderia electrophaga' compared to those on plain glass. Addition of metabolic inhibitors showed that living cells were required to maintain the more positive potential. We propose a model to describe these observations, in which ' Ca . Tenderia electrophaga' drives the shift in open circuit potential through electron uptake for oxygen reduction and CO2 fixation. We further propose that the electrode is continuously recharged by oxidation of trace redox‐active molecules in the medium at the more positive potential. A similar phenomenon is possible on natural conductive substrates in the environment.